Case Report: Asymptomatic macular edema in ozanimod - Mauceri, Valentina Annamaria; Torresin, Tommaso; Basili, Elisa; Gaggiola, Marta; Rinaldi, Francesca; Baroni, Francesco; Gallo, Paolo; Perini, Paola; Pilotto, Elisabetta; Puthenparampil, Marco (Frontiers in Ophthalmology, 2025)
We report the case of a 61-year-old patient with relapsing–remitting multiple sclerosis (RRMS) who developed asymptomatic macular edema (ME) after initiation of ozanimod, a sphingosine-1-phosphate receptor (S1PR) modulator. The patient had a history of completely resolved central serous choroidopathy (CSC) in the right eye. Following a recent clinical worsening and a new brain lesion, ozanimod was started after appropriate screening, including ophthalmological evaluation. Three months into treatment, an OCT performed as part of routine monitoring revealed ME in the contralateral (left) eye, despite the absence of visual symptoms. Ozanimod was discontinued, and ME progressively resolved over the subsequent 2 months. This case underscores the importance of ophthalmological monitoring even in asymptomatic patients, especially those with known risk factors such as prior retinal pathology. ME is a rare but recognized adverse event associated with all approved -imod therapies for MS, including ozanimod. Although the exact pathophysiology remains unclear, involvement of the inner blood–retina barrier via S1PR1 internalization has been hypothesized. Given ozanimod’s long half-life and active metabolites, ME resolution may be delayed after drug withdrawal. This report highlights the relevance of interdisciplinary management and the utility of OCT in early detection of asymptomatic ocular adverse events during S1PR modulator therapy.